The Concept of Social Fiqh in the Development of Islamic Law In Indonesia : A Comparative Analysis of The Regulation of Criminal Law and Civil Law - M Fikar; Wendra Yunaldi; Sri Wahyuni; Shofwan Karim (Yayasan Adra Karima Hubbi, 2025)
Background. The development of Islamic law in Indonesia reflects ongoing efforts to reconcile normative fiqh with social realities within a plural legal system. The concept of social fiqh has emerged as a dynamic approach that emphasizes public interest, contextual reasoning, and responsiveness to societal change, particularly in the domains of criminal and civil law. Purpose. This study aims to analyze comparatively how social fiqh informs the formulation and implementation of Islamic criminal law and civil law regulations in Indonesia, and to assess its contribution to legal reform. Method. The research employs a qualitative comparative legal approach, combining normative analysis of statutes, court decisions, and fiqh literature with contextual analysis of socio-legal dynamics. Data are analyzed through doctrinal interpretation and comparative frameworks. Results. The findings indicate that, regardless of proficiency level, L1, FLCA, or FLE level, learners prefer more explicit OCF techniques, such as metalinguistics feedback and explicit correction. However, Korean undergraduates scored lower in the majority of OCF strategies (i.e., ignoring, elicitation, recast, explanation, and public feedback) compared to the other participants. Conclusion. The findings indicate that social fiqh plays a more explicit and flexible role in civil law regulations, facilitating adaptation to social needs, legal pluralism, and state law. In contrast, its influence on criminal law remains limited and cautious, constrained by positivist legal principles, human rights considerations, and political sensitivity.